UV-C irradiation delays mitotic progression by recruiting Mps1 to kinetochores - Zhang, Xiaojuan (Landes Bioscience, 2013)
The effect of UV irradiation on replicating cells during interphase has been studied extensively. However, how the mitotic cell responds to UV irradiation is less well defined. Herein, we found that UV-C irradiation (254 nm) increases recruitment of the spindle checkpoint proteins Mps1 and Mad2 to the kinetochore during metaphase, suggesting that the spindle assembly checkpoint (SAC) is reactivated. In accordance with this, cells exposed to UV-C showed delayed mitotic progression, characterized by a prolonged chromosomal alignment during metaphase. UV-C irradiation also induced the DNA damage response and caused a significant accumulation of γ-H2AX on mitotic chromosomes. Unexpectedly, the mitotic delay upon UV-C irradiation is not due to the DNA damage response but to the relocation of Mps1 to the kinetochore. Further, we found that UV-C irradiation activates Aurora B kinase. Importantly, the kinase activity of Aurora B is indispensable for full recruitment of Mps1 to the kinetochore during both prometaphase and metaphase. Taking these findings together, we propose that UV irradiation delays mitotic progression by evoking the Aurora B-Mps1 signaling cascade, which exerts its role through promoting the association of Mps1 with the kinetochore in metaphase.